2006
DOI: 10.1007/s00223-006-0111-6
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Promoter Element within the Zebrafish colXα1 Gene Responsive to Runx2 Isoforms Osf2/Cbfa1 and til-1 but not to pebp2αA2

Abstract: Type X collagen is a short chain collagen specifically expressed by hypertrophic chondrocytes during endochondral ossification. We report here the functional analysis of the zebrafish (Danio rerio) collagen Xalpha1 gene (colXalpha1) promoter with the identification of a region responsive to two isoforms of the runt domain transcription factor runx2. Furthermore, we provide evidence for the presence of dual promoter usage in zebrafish, a finding that should be important to further understanding of the regulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
25
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 43 publications
4
25
0
Order By: Relevance
“…As reported previously (Simoes et al, 2006), we found that the col10a1 promoter contains 2 Runx2 consensus binding sequences (PuACCPu-CA/TGTGGT) upstream of the predicted transcriptional start site (TSS, -812 and -66 positions) and an additional binding site at the +23 position from the TSS (Fig. 2).…”
Section: Resultssupporting
confidence: 82%
See 3 more Smart Citations
“…As reported previously (Simoes et al, 2006), we found that the col10a1 promoter contains 2 Runx2 consensus binding sequences (PuACCPu-CA/TGTGGT) upstream of the predicted transcriptional start site (TSS, -812 and -66 positions) and an additional binding site at the +23 position from the TSS (Fig. 2).…”
Section: Resultssupporting
confidence: 82%
“…Previous studies have suggested that the col10a1 promoter of vertebrates may contain several components that direct its tissue-specific gene expression, such as the proximal basal regulatory region, and negative and positive regulatory elements (Higashikawa et al, 2009;Li et al, 2011;Simoes et al, 2006;Zheng et al, 2003). Our study also supports the existence of different regulatory elements within the zebrafish col10a1 promoter at least for the osteoblast-specific program.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Type X collagen (Col10a1) is a marker of both osteoblasts and maturing chondrocytes in teleosts (Avaron et al, 2006; Clement et al, 2008; Simoes et al, 2006). In wild types, whole-mount in situ hybridization at 5 dpf showed that col10a1 is expressed in osteoblasts of both the endochondral (e.g., ceratohyal, hyomandibular) and intramembranous (e.g., opercle, dentary) skeletons (Fig.…”
Section: Resultsmentioning
confidence: 99%